Stem anteversion mismatch to the anatomical anteversion causes loss of periprosthetic bone density after THA - Shinya Hayashi (Journal of Orthopaedic Surgery, 2017)
The short tapered-wedge stem is popular worldwide because it potentially preserves more bone stock during total hip arthroplasty (THA). However, stem version mismatch may affect physiological stress distribution. In this study, we analyzed the correlations between periprosthetic bone mineral density (BMD) changes and anteversion mismatch in patients who underwent THA using a short tapered-wedge stem. The study included 44 patients (44 joints) who underwent THA with a Tri-Lock stem. At baseline and at 6 and 24 months postoperatively, the BMDs in the seven Gruen zones were evaluated using dual-energy X-ray absorptiometry. BMD changes and stem alignment, that is, anteversion and stem anteversion mismatch to the anatomical canal anteversion, were analyzed. Significant negative correlations were found between BMD changes and absolute anteversion error in Gruen zones 1 and 7 at 6 and 24 months postoperatively (zone 1, 6M; RR= −0.48, p < 0.001) (zone 7, 6M; RR= −0.46, p = 0.002) (zone 1, 24M; RR= −0.47, p = 0.001) (zone 7, 24M; RR= −0.40, p = 0.007). We further demonstrated that excessive stem anteversion mismatch to the anatomical canal anteversion causes stem point contact with the cortical bone in the distal portion and affected proximal periprosthetic BMD loss after THA. We recommend that the native anatomical anteversion angle should be used as a reference for inserting the tapered-wedge stems.